Evaluation of mucoadhesive carrier adjuvant: Toward an oral anthrax vaccine. (February 2014) - Mangal, Sharad; Pawar, Dilip; Agrawal, Udita; Jain, Arvind K.; Vyas, Suresh P.
Abstract The aim of present study was to evaluate the potential of mucoadhesive alginate-coated chitosan microparticles (A-CHMp) for oral vaccine against anthrax. The zeta potential of A-CHMp was − 29.7 mV, and alginate coating could prevent the burst release of antigen in simulated gastric fluid. The results indicated that A-CHMp was mucoadhesive in nature and transported it to the peyer's patch upon oral delivery. The immunization studies indicated that A-CHMp resulted in the induction of potent systemic and mucosal immune responses, whereas alum-adjuvanted rPA could induce only systemic immune response. Thus, A-CHMp represents a promising acid carrier adjuvant for oral immunization against anthrax.